A graphene-based THz metasurface sensor with air-spaced structure - Hu, Hui; Qi, Bin; Zhao, Yufan; Zhang, Xiaoju; Wang, Yue; Huang, Xinning (Frontiers in Physics, 2022)
Owing to the unique electromagnetic response ability, electromagnetic metasurface have potential applications in medical, imaging, sensing, and other fields. In this paper, a graphene-based THz metasurface sensor with an air spacer layer is designed by combining the advantages of the air spacer structure and the dynamic tunability of graphene materials. The proposed metasurface sensor consists of six layers, which are silicon dioxide (SiO2) substrate, metal reflector, air layer, graphene metasurface etched with microstructure, ion-gel layer and silicon dioxide dielectric layer from bottom to top. A comprehensive study of the absorption properties and sensing performance are carried out which is simulated and analyzed with the help of CST Microwave Studio software. The calculation results show that the two obvious resonance absorption peaks located at 0.95 THz and 1.53 THz with absorption of 94.9% and 79%, respectively, and there is a good linear relationship between the absorption peak and dielectric parameters of analyte. The frequency shift sensitivity of the two resonance peaks M1 and M2 can reach 450 GHz/RIU and 717 GHz/RIU, respectively. By changing the thickness of the air layer, when the two resonance peaks M1 and M2 reach the maximum absorption at h2 = 140um and h2 = 280um, respectively, the frequency shift sensitivity is still as high as close to 450 GHz/RIU. The influence of structure parameters and incident angle on the absorption spectrum shows that the proposed structure has good stability and reliability. The proposed graphene-based absorption sensor has good biocompatibility, broadening the application range of terahertz functional devices.